Статистический анализ показателей функционального состояния человека в эргатической системе «человек–компьютер» - Страхова, О. П.; Рыжов, А. А.; Рижов, Олексій Анатолійович (Харьков, 2014)
Abstract Introduction. Modern learning process is designed for the widespread use of computers. Such ergatic learning environment can have the influence at the changes in the students’ functional state. Purpose. To establish such an influence, and what are its quantitative indicators. Results. Statistical processing of the study results revealed significant changes of monitored parameters at a person’s functional state after class held in ergatic learning environment. Conclusion. Is established a significant correlation between electrocutaneous characteristics microzones changes and the parameters of heart rate variability and upper limbs rheovasography
Statistical analysis the index of human functional state in ergatic system «human–computer»
Keywords: Electrocutaneous characteristics of micro-zones; Statistical analysis; Correlation; Heart rate variability; Upper limbs rheovasography